Pharmacological Activity of Newly Synthesized and Characterized N, O-donor Tetraaza Macrocyclic Metal Complexes - Jain, Preeti (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To synthesize a new series of metal based therapeutic agents with good antimicrobial and antioxidant properties and their structural characterization. Methodology: Synthesis of a series of transition metal complexes of type [M(C16 H11N4O2)X2], where M=Co(II), Ni(II), and Cu(II), X = Cl−, NO3− and CH3COO−derived from template condensation of 1,3-dicarbonyl-phenyl-dihydrazide and 1H-indole-2,3-dione(isatin) and their characterization by ultraviolet-visible, Fourier-transformed infrared spectroscopy, electron paramagnetic resonance, mass spectral studies. Antimicrobial activity was determined using agar well diffusion method against four bacterial strains and two fungal strains. Antioxidant potential of compounds was screened by 2, 2-diphenyl-1- picrylhydrazyl scavenging activity method. Result: All the synthesized complexes were found to have six coordinated octahedral geometry. All test compounds possess varied but significant antimicrobial activity against four bacterial and two yeast strains. Minimum inhibitory concentrations lie between 32-128 μg/ml for the bacterial strains. Some of the test compounds have shown significant % radical scavenging activity. Conclusion: Tetradentate ligand derived from template condensation coordinates readily with all divalent metal salts and affords the synthesis of octahedral complexes. Detailed structural and biological investigation of this series of complexes would throw more light on the influence of metal coordination on the reactivity of macrocyclic molecules which may be further explored and used as alternative therapeutic agents.